From Manila, with love a balikbayan story - Capelle, Amabel. L.; Yambao, Auri A. (Makati City Tahanan Books for Young Readers, 2015)
"What does it mean to "come home" for the first time? Here is a story that tenderly captures the incomparable joy of the balikbayan experience."
Keywords: Readers (Elementary) -- Juvenile fiction; Manila (Philippines) -- Description and travel -- Juvenile fiction; Children's stories, Philippines (English).